The Influence of Circuit Training on Physical Conditions of Sports Training Education Students - Wijayanti, Ni Putu Nita; Mandan, Ali; Sari, Tri Kurnia (Proceedings of the UR International Conference on Educational Sciences, 2018)
The Problems that occur during the lecture process of female students in 2015wastheir result relatively far below the average of the male student.This can be seen in the recapitulation of the value of the subjects in the 2015/2016 odd semester that was 74 for the female, and 82 for the male student. Other data that proved the problemwas when the initial physical condition test was conducted for the Physical condition development course on February 13, 2018, the same problem occurs for the 2015 class year student. The result shows that 87.5% or 7 out of 7 female students have physical conditions in fewer categories. The circuit training method was used to improve the physical condition of a student. In this study, researchers took 7 female population. The sample in this study used a total sampling technique, so the sample in this study amounted to 7 students. The data was obtained from physical condition tests. The results obtained from pretest and posttest were analyzed by t-test. Based on the t-test, it yielded counted t of 2.313 with tabled t 2.015 then Ha was rejected, at alpha level (Î±) of 0.05. It can be concluded that there is an effect of circuit training on the physical condition of female class B trainees in sports training in 2015.